Spleen cell proliferation during and after skin myiasis by human bot fly Dermatobia hominis Proliferação de células do baço durante e após miíase por Dermatobia hominis - Jomara Mendes Gonçalves; Maria Fernanda Alves do Nascimento; Natália Martins Breyner; Viviane Cristina Fernandes; Alfredo Miranda de Góes; Antonio César Rios Leite (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
Spleen cells from mice were examined at 5, 10, 15, 20 and 25 days post-infection (dpi) with Dermatobia hominis larva and at 5, 10, 15, 30 and 60 days post-larval emergence (dple). Cell proliferation in vitro assays were carried out with RPMI-1640 medium and larval secretory product (LSP) of D. hominis at 5, 10, 15, 20 and 25 days. When each group of mice was tested against each medium, significance was only seen for 25 dpi, with increasing order: LSP-10 d, -25 d, -5 d, -20 d, -15 d and RPMI. Significant results were also observed when each medium was tested against mice at each dpi or dple. Each dple group vs. each medium produced significant results only for 10 dple, with increasing order: LSP-5 d, -20 d, -25 d, -10 d, -15 d and RPMI. Comparative tests were also carried out between groups to refine certain observations. The LSPs were also analyzed using SDS-PAGE. The results prove that myiasis caused depletion of spleen cells, particularly under the effect of the LSP-10 and -15, but the cells tended to increase up to 60 dple. This in vitro assay may represent the real systemic immune response in the relationship LSP-D. hominis-host. Células do baço de camundongos foram examinadas aos 5, 10, 20 e 25 dias pós-infecção (dpi) com Dermatobia hominis e examinadas aos 5, 10, 15, 30 e 60 dias pós-emergência da larva (dpel). As células foram cultivadas em meio RPMI-1640 contendo, ou não (controle), produtos de secreção das larvas (PSL) de D. hominis com idade de 5, 10, 15, 20 e 25 dias. Em cada grupo com cinco camundongos testados nos meios de cultura, o número de células foi significativo para 25 dpi, com crescente aumento na seguinte ordem: PSL-10 d, -25 d, -5 d, -20 d, -15 d e RPMI. Resultados significantes foram também observados nos testes entre cada meio contendo células tanto de camundongos dpi ou dpel. Em cada dpel grupo versus meio significância foi somente verificada para 10 dpel, na ordem crescente: PSL-5 d, -20 d, -25 d, -10 d, -15 d e RPMI. Testes comparativos foram também realizados entre grupos. O PSL foi analisado sob SDS-PAGE. Os resultados provam que a miíase causou depleção de células do baço, particularmente sob efeito do PSL-10 e -15, mas ocorreu normalidade do número de células aos 60 dpel. Este ensaio in vitro pode representar uma resposta imune sistêmica na relação PSL-D. hominis-hospedeiro.